Case Report: EBV-Positive Extra-Nodal Marginal Zone Lymphoma Associated With XMEN Disease Caused by a Novel Hemizygous Mutation in MAGT1 - Huang, Xin; Liu, Dan; Gao, Zifen; Liu, Cuiling (Frontiers in Oncology, 2021)
Background: X-linked immunodeficiency with magnesium defect and Epstein-Barr virus infection and neoplasia (XMEN) disease is an X-linked genetic disorder of immune system caused by loss-of-function mutation in gene encoding Magnesium transporter 1 (MAGT1). Individuals with XMEN disease are prone to developing Epstein Barr Virus (EBV)-associated lymphomas. Herein, we report the first known case of an EBV+ EMZL associated with XMEN disease. Case presentation: The patient was an 8-year-old Chinese boy who suffered from recurrent infections from birth. Six months before, the patient presented with a painless mass on his upper lip and excisional biopsy revealed an EBV-positive extra-nodal marginal zone lymphoma (EBV+ EMZL). Furthermore, molecular investigations with next-generation sequencing identified a novel germline mutation in MAGT1 (c.828_829insAT) in the patient. The c.828_829insAT variant was predicted to cause premature truncation of MAGT1 (p.A277M.fs*11) and consequently was defined as likely pathogenic. The mutation was inherited from his asymptomatic heterozygous carrier mother. Hence the patient was diagnosed with an XMEN disease both clinically and genetically. Conclusion: Our results expand the genetic spectrum of XMEN disease and also the clinical spectrum of EBV+ EMZL. We highlights the importance of the genetic etiology underlying EBV+ lymphoma in the pediatric population.